Understanding the ESG and Financial Performance Relationship: Different Metrics Matters - Widyawati, Luluk (Perspektif Akuntansi, 2024)
Studies on the relationship between environmental, social, and governance (ESG) and a firm's financial performance remain largely inconclusive. This study attempts to provide empirical evidence that the disagreement among ESG ratings lead to the different results of firm-level studies on the relationship between ESG and financial performance. Tests of multiple models using different ESG rating uncover three types of variations: statistical significance, directionality, and magnitude. This study also indicates that the effect is greater in studies on accounting-based financial performance measures and studies applying composite ESG score. Social dimension consistently presents the highest number of variations compared to environmental and governance dimensions.